Relationship of depression with empathy, emotional intelligence, and symptoms of a weakened immune system - Grases, Gloria; Colom, Maria Antonia; Sanchis, Pilar; Grases, Felix (Frontiers in Psychology, 2023)
Introduction: Previous studies have used different individual scales to examine the relationship of depression with emotional intelligence, empathy, and immune-based diseases. In this study, we used a combination of psychometric scales to examine the relationships of depression with emotional intelligence (intrapersonal and interpersonal), empathy (affective and cognitive), and symptoms of weakened immune system.This cross-sectional prospective study examined 158 volunteers (39 males and 119 females). A score of 10 or more on the Beck Depression Inventory-II (BDI-II) was used to define depression. The Cognitive and Affective Empathy Test (TECA) was used to assess empathy, and the Profile of Emotional Competence (PEC) was used to assess the self-perception of intrapersonal and interpersonal competence. The symptoms of a weakened immune system (WIS) were assessed by measurements of permanent tiredness, frequent infections and colds, slow wound healing, persistent and recurrent diarrhea, recurring herpes, insomnia and difficulty sleeping, and dry eyes.The total PEC score and intrapersonal PEC score had negative correlations with depression, and the WIS score had a positive correlation with depression. The TECA score had no significant correlation with depression or the WIS score, but had positive correlations with the total PEC score, intrapersonal PEC score, and interpersonal PEC score.The total PEC score, intrapersonal PEC score, and WIS score were significantly associated with depression. The TECA score was not significantly associated with depression or the WIS score. Our findings suggest that improving intrapersonal emotional skills may improve function of the immune system and reduce the symptoms of depression. We suggest that further studies examine the effect of targeted improvement of interpersonal skills (empathy) on depression.This study analyzed the possible associations among depression, emotional intelligence (intrapersonal and interpersonal), empathy (affective and cognitive), and symptoms of a weakened immune system in adults.